2010
DOI: 10.1007/s11671-010-9771-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Low-Density Vertical Quantum Dot Molecules with Control in Energy Emission

Abstract: In this work, we present results on the formation of vertical molecule structures formed by two vertically aligned InAs quantum dots (QD) in which a deliberate control of energy emission is achieved. The emission energy of the first layer of QD forming the molecule can be tuned by the deposition of controlled amounts of InAs at a nanohole template formed by GaAs droplet epitaxy. The QD of the second layer are formed directly on top of the buried ones by a strain-driven process. In this way, either symmetric or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Recently, Alonso‐González et al demonstrated a nanohole template‐assisted growth technique, which can be used to form QDPs with controllable density . A illustration of the VQDP sample structure is shown in Figure a.…”
Section: Vertically Aligned Quantum Dot Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Alonso‐González et al demonstrated a nanohole template‐assisted growth technique, which can be used to form QDPs with controllable density . A illustration of the VQDP sample structure is shown in Figure a.…”
Section: Vertically Aligned Quantum Dot Pairsmentioning
confidence: 99%
“…After forming of InAs QDs and a partial GaAs capping layer of about 5 nm, “indium‐flush” is carried out to obtain homogeneous QDs in plane and uniform vertically aligned QDs. Recently, Alonso‐González et al have also fabricated vertical QDPs by using a droplet epitaxy patterning process. Instead of directly forming InAs QDs on an atomic flat GaAs surface, the first layer of InAs QDs is deposited on a nanohole template fabricated by droplet epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Lately especial attention has been given to the problem of well organized lowdimensional objects, which opens new perspectives for the manipulation of electronic and optical properties of matter and thus the possibility of creating devices on the base of new effects [3]. The new technological methods are developed based on standard technologies for producing semiconductor heterostructures like molecular beam epitaxy (MBE) and metalorganic chemical vapour deposition (MOCVD), allowing to control mutual positions and orientation of nano-size objects within heterostructures; for example, vertically stacked InGaAs/GaAs(001) QWW and QD chains were prepared using MBE method [4] and vertical artificial molecular structures formed by two vertically aligned InAs QDs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods to fabricate vertically coupled QDs have been demonstrated ranging from QDPs generated beneath lithographically patterned gate structures [3,4] to various self-assembling techniques based on the Stranski-Krastanov (SK) QD growth [5][6][7][8][9][10]. The former are mainly used in transport experiments [3,4], while the latter are optimal for optical experiments.…”
Section: Introductionmentioning
confidence: 99%